2014
DOI: 10.1007/s00198-014-2627-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pulmonary function and bone mineral density in healthy nonsmoking women: the Korean National Health and Nutrition Examination Survey (KNHANES) 2010

Abstract: Pulmonary function, including FVC and FEV1 are associated with BMD at FN in healthy nonsmoking premenopausal women but not in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…A South Korean study that enrolled 456 premenopausal women who had never smoked showed that FVC and FEV 1 were correlated with BMD. 39 This is consistent with our findings showing that FEV 1 is an independent risk factor regardless of smoking history.…”
Section: Discussionsupporting
confidence: 93%
“…A South Korean study that enrolled 456 premenopausal women who had never smoked showed that FVC and FEV 1 were correlated with BMD. 39 This is consistent with our findings showing that FEV 1 is an independent risk factor regardless of smoking history.…”
Section: Discussionsupporting
confidence: 93%
“…This result was lower than the prevalence in other COPD studies and higher than that in the general population. [ 6 16 17 18 ] Studies have shown that patients with COPD usually have low BMD, impaired bone quality, and low bone turnover. [ 4 ] The mechanisms by which osteoporosis occurs in COPD patients are not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 22 23 ] The correlation between BMD and FEV 1 has also been demonstrated in the general population. Jeon et al[ 17 ] reported that FVC and FEV 1 are associated with BMD in healthy nonsmoking premenopausal women but not in postmenopausal women. Lee et al[ 24 ] found that FEV 1 was negatively correlated with lumbar spine BMD but not femur neck or total hip BMD in middle-aged Korean men.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased forced expiratory volume in one second (FEV1.0) and/or advanced Global Initiative for Chronic Obstructive Lung Disease (GOLD) stages have been demonstrated to be correlated with lower BMD. [ 6 8 10 27 37 ] Some [ 81 82 ] but not all [ 83 ] have reported correlation between BMD and FEV1.0 in the general population. In COPD patients the correlation of pulmonary function and/or GOLD stages with BMD seems to be in part mediated by BMI, whereas the correlation between BMD and with fracture prevalence was not always apparent.…”
Section: Disease-specific Risk Factors For Osteoporosis In Copdmentioning
confidence: 99%